Kegiatan Petani dalam Pengadaan Sarana Produksi Padi Sawah di Desa Atari Jaya Kecamatan Lalembuu Kabupaten Konawe Selatan - Hulzana, Austia Mifta; Buana, Tjandra; Mardin, Mardin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
The research objective was to determine the Farmers in procurement activities on facing scarcity at rice production means in Atari Jaya Village Subdistrict Lalembuu at District South Konawe. This study was conducted from October 20 until November 15, 2016 in the Atari Jaya Village subdistrict Lalembuu at South Konawe . The number of samples is as much as 45 farmers who each represent a group of farmers, from the population of 224 heads of family farmers. The analytical tool used to achieve the purpose of the study is a qualitative research approach further percentage descriptively narrated to answer the research problems. Research results revealed that activity Village farmers Atari Jaya in the procurement of inputs based on the priority scale is as follows: the creation of warehouses for storage of stock of inputs that will be used in the next planting season, the next is the activity of using organic fertilizer to replace chemical fertilizers and maintaining soil fertility and activities the latter is next is to make a proposal request for help means rice production to the government. Conclusion The research activities of farmers in the provision of means of rice production were: 1) to build a warehouse; 2) the use of organic fertilizers; and 3) make proposals to the government for assistance